Implementing IT-Based Succession Planning in University IT Units: Enhancing Operational Continuity - Yualinda, Sherla; Adi, Taufik Nur; Fakhurroja, Hanif; Yualinda, Sherli (Journal of Information System and Informatics, 2025)
One of the accredited universities in Indonesia is committed to quality education through the use of information technology. However, the university's IT unit often experiences vacancies in key positions due to high employee turnover, which impacts workload and business processes, especially in handling Request for Change (RFC). While application X supports performance appraisals, it has not been optimized for succession planning. This study explores the potential of application X as a tool for succession planning by integrating the Rothwell and Integrated Talent Management models. The design includes identifying key positions, assessing candidate competencies, preparing development plans, and establishing a structured knowledge transfer system to sustain organizational leadership. Additionally, integrating Large Language Models (LLMs) like ChatGPT is expected to enhance assessment objectivity, provide individual development recommendations, and ensure a more effective leadership transition. The system's role in improving assessment objectivity is vital for unbiased, data-driven decisions, while its contribution to leadership transitions ensures a smoother, more systematic process for maintaining leadership continuity. With features such as candidate search and staff assessment, the system is expected to help organizations select the right replacement and maintain university operations.